2022
DOI: 10.1002/chem.202201068
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahalidometallate(II) Ionic Liquids with More than One Metal: The Effect of Bromide versus Chloride

Abstract: Fifteen N-butylpyridinium salts -five monometallic [C 4 Py] 2 [MBr 4 ] and ten bimetallic [C 4 Py] 2 [M 0.5 a M 0.5 bBr 4 ] (M=Co, Cu, Mn, Ni, Zn) -were synthesized, and their structures and thermal and electrochemical properties were studied. All the compounds are ionic liquids (ILs) with melting points between 64 and 101 °C. Powder and single-crystal X-ray diffraction show that all ILs are isostructural. The electrochemical stability windows of the ILs are between 2 and 3 V.The conductivities at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…The crystal structures are closely related to the existing examples 23,28,33,42 and these data clearly show that the process and approach towards these ILs is highly reproducible, exible, and adaptable. Moreover, like on the previous examples, all structures of the single crystals (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The crystal structures are closely related to the existing examples 23,28,33,42 and these data clearly show that the process and approach towards these ILs is highly reproducible, exible, and adaptable. Moreover, like on the previous examples, all structures of the single crystals (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, Balischewski et al have recently shown that the combination of two or three metal ions in MX 4 2− -based ILs leads to ILs with a range of colors from blue to green to yellow and orange, although no tests on their sensing capabilities have been made so far. 23,28 The current article extends the previous work in two directions: (1) it expands the pool of mixed d-metal-based ILs to new bimetallic ILs built around Ni(II) and Zn(II) and (2) the article also demonstrates that the compounds can be used as the active component in an optical setup for the detection of ammonia gas using a ber optic probe and a simple IL-coated glass slide.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations